1994
DOI: 10.2172/10171709
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of operational experience during low power and shutdown and a plan for addressing human reliability assessment issues

Abstract: Recent nuclear power plant events (e.g., Chernobyl, Diablo Canyon, and Vogtle) and U.S. Nuclear Regulatory Commission (NRC) reports (e.g., NUREG-1449) have led to concerns regarding human reliability during low power and shutdown (LP&S) conditions and limitations of human reliability analysis (HRA) methodologies in adequately representing the LP&S environment. As a result of these concerns, the NRC initiated two parallel research projects to assess the influence of LP&S conditions on human reliability through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In the event descriptions in LERs, there was insufficient information to identify separate unsafe actions, or the existence of dependence mechanisms. The limitations in LER reports as a basis for HRA modeling were discussed in NUREG/CR-6093 (Barriere et al, 1994b).…”
Section: Analysis Of Dependencies In Event Datamentioning
confidence: 99%
See 3 more Smart Citations
“…In the event descriptions in LERs, there was insufficient information to identify separate unsafe actions, or the existence of dependence mechanisms. The limitations in LER reports as a basis for HRA modeling were discussed in NUREG/CR-6093 (Barriere et al, 1994b).…”
Section: Analysis Of Dependencies In Event Datamentioning
confidence: 99%
“…Several necessary improvements to the HACS database (Barriere et al, 1994b), have been identified, related principally to the evolution of the project, our current understanding of human performance, and the associated unanticipated needs of research and development (e.g., framework, EOCs, and dependencies). Consequently, it is important to update and improve the structure of the database scheme and user-interface to support current and future work.…”
Section: Database Imdrovement Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first database, the Human Action Classification Scheme (HACS) (Barriere, Luckas, Whitehead, and Ramey-Smith, 1994) pre-dates ATHEANA. It was patterned on existing databases, including the Human Performance Investigation Process (HPIP) (Paradies, Unger, Haas, and Terranova, 1993) and the Nuclear Computerized Library for Assessing Reactor Reliability (NUCLARR) (Gilbert, Gertman, and Gilmore, 1990) , so represented the commonly accepted aspects of human performance such as performance shaping factors (PSFs), event time phases, and error types.…”
Section: Introductionmentioning
confidence: 99%